KONSEPSI KEBIJAKAN PEMERINTAH DI ERA NEW NORMAL - Muhammad Qur’anul Kariem (TheJournalish: Social and Government, 2020)
The government has a formalistic conception of public policy with regulatory guidelines (laws and regulations). The public policy is carried out by state apparatuses working within the framework of procedural government bureaucracy. In the New Normal era the government should be able to change or at least shift the paradigm of governance that impacts on bureaucracy and public policy. This article describes how the government can use several methods to run the government in the uncertainty of almost all people's lives, both social, economic, health.